Biodentine® and its temporary use. Literature review - Wyssenbach - Kanpandegia, Elena (2020)
Biocompatibility and bioactivity have become almost indispensable characteristics in any dental material. Re-cently we have the Biodentine®. It is a cement with high physical-mecanical properties that began to be mar-keted in 2009 and was specially designed as a dentin substitute. For pediatric dentistry this search for new effective, resistant and biocompatible materials is especially important in some treatments such as pulpotomy in which the classically used drugs, such as formocresol, have been removed from clinical use due to their toxic potential. Due, on the one hand, to a greater use of Biodentine® in the dental clinic, especially in the odontopediatric treatment, and on the other hand, to be greater scientific production in this respect, it has been thought convenient to carry out this revision of the literature with the aim of deepening the updated knowledge of this material especially of its use in odontopediatrics.